Implementasi Model Problem Based Learning dalam Meningkatkan Hasil Belajar Pendidikan Agama Islam - Asyitaa Inayatullah; Afifuddin Ahmad Robbani; Wakib Kurniawan (Jurnal Dirosah Islamiyah, 2026)
This research is motivated by the dominance of textual memorization methods (rote learning) in Islamic Religious Education (PAI) subjects in elementary schools, which often make religious material feel abstract and separated from students' social reality. The purpose of this study is to analyze the implementation of the Problem-Based Learning (PBL) model based on ill-structured problems, the process of providing scaffolding in students' Zone of Proximal Development (ZPD), and its impact on students' cognitive, affective, and psychomotor transformations. The method used is descriptive qualitative with a single case study design at Al Hadiid Islamic Elementary School. Data were collected through participatory observation, in-depth interviews with teachers and students, and documentation of students' physical work, which were then analyzed using data reduction, data presentation, and conclusion drawing techniques. The results show that the deconstruction of PAI material into open, real-world problems successfully sparked students' intrinsic curiosity and built the character of mutual cooperation (Ta'awun). The provision of structured assistance (scaffolding) gradually proved effective in generating learning autonomy when students' competencies reached the ZPD limit. Furthermore, the PBL model successfully integrated the achievements of the three domains of learning outcomes in a balanced manner, improving critical thinking skills (C4-C5), and reconstructing students' paradigms in viewing Islam not merely as exam material but as a real-life moral compass (way of life). Heterogeneous group dynamics also validated the application of the principles of reciprocal determinism and positive imitation (peer modeling) that are humanistic among students. This study concludes that PBL is an effective catalyst for shifting the orientation of Islamic Religious Education learning from textual to contextual (kaffah).